2000
DOI: 10.1021/tx000180q
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Metabolism of Troglitazone to Reactive Intermediates in Vitro and in Vivo. Evidence for Novel Biotransformation Pathways Involving Quinone Methide Formation and Thiazolidinedione Ring Scission

Abstract: Therapy with the oral antidiabetic agent troglitazone (Rezulin) has been associated with cases of severe hepatotoxicity and drug-induced liver failure, which led to the recent withdrawal of the product from the U.S. market. While the mechanism of this toxicity remains unknown, it is possible that chemically reactive metabolites of the drug play a causative role. In an effort to address this possibility, this study was undertaken to determine whether troglitazone undergoes metabolism in human liver microsomal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
253
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(275 citation statements)
references
References 17 publications
19
253
2
Order By: Relevance
“…For conjugates 1 and 2, conjugation at the methyl is likely to occur through the formation of a quinone methide intermediate. While this has been observed previously in GST conjugation to methyl-substituted aromatic rings (Kassahun et al, 2001;Li et al, 2009), this is, to our knowledge, the first report of such a GST conjugate to TNT. For both GST-U24 and GST-U25, catalytic activity increased with pH, with the optimum appearing to be pH 9.5 or greater.…”
Section: Glutathione-tnt Productssupporting
confidence: 73%
“…For conjugates 1 and 2, conjugation at the methyl is likely to occur through the formation of a quinone methide intermediate. While this has been observed previously in GST conjugation to methyl-substituted aromatic rings (Kassahun et al, 2001;Li et al, 2009), this is, to our knowledge, the first report of such a GST conjugate to TNT. For both GST-U24 and GST-U25, catalytic activity increased with pH, with the optimum appearing to be pH 9.5 or greater.…”
Section: Glutathione-tnt Productssupporting
confidence: 73%
“…The use of thiazolidinediones is limited due to their toxicity, and some authors have related this toxicity to the formation of thiazolidinedione ring opening metabolites in troglitazone (Kassahun et al, 2001), which is a common pathway for other thiazolidinediones (Baughman, 2005;Alvarez-Sánchez et al, 2006;Shen et al, 2008). These opened ring metabolites have been previously reported (Uchiyama et al, 2010), and two of them (M-B and M-C) were observed in our work.…”
Section: Discussionsupporting
confidence: 69%
“…With the recent publication of the Guidance for Metabolite Safety Testing (FDA, 2008), metabolite investigations have become even more important (Baillie, 2008;Leclercq et al, 2009). Considering thiazolidinediones, it was proposed that the ring-opened may be related to formation of reactive metabolites of troglitazone (Kassahun et al, 2001). This ring opening mechanism is common to other thiazolidinediones (Alvarez-Sánchez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The peripheral site for the substrate has a possible structural basis in some of the X-ray crystal structures of P450 3A4 [31,32], although the possibility FIGURE 5. An example of a bioactivation of a drug (troglitazone) to electrophilic products tagged by glutathione (GSH) [38,39]. that binding at that site is an artifact cannot be dismissed.…”
Section: Figurementioning
confidence: 99%
“…However, these can all be rationalized in the context of the proposed perferryl oxidation chemistry discussed above, and the reader is referred to more extensive reviews published elsewhere [8,36,37]. In a number of cases the, oxidized products are electrophilic and the binding of these to tissue nucleophiles can be related to toxicity ( Figure 5) [38][39][40][41], although demonstration of a causal relationship has proven difficult [42].…”
Section: Unusual P450 Reactions and Reactive Electrophilic Productsmentioning
confidence: 99%